PERUBAHAN JUMLAH MIKROBA SEBELUM DAN SESUDAH CUCI TANGAN MENGGUNAKAN SABUN ANTIBAKTERI PADA MAHASISWA AKADEMI KESEHATAN GIGI DITKESAD TAHUN 2019 - Sulistiani, Silvia; Athallah, Tomy (E-Journal Widya Kesehatan dan Lingkungan, 2020)
Hand washing is one step that can be done to prevent the spread of disease. This study aims to determine changes in the number of microbes in the hands before and after washing hands using antibacterial soap in AKG Ditkesad students. The research design used in this study was cross sectional analysis. The method used is descriptive research conducted to describe a phenomenon that occurs in society. Research respondents numbered 50 students. Sampling used quota sampling technique. Respondents were asked to put their index fingers on sheep's blood media for a few seconds both before and after washing hands. Media is incubated and changes in the area of ​​bacteria in the media was observed. There is a significant difference between the area of ​​bacteria on blood agar before and after washing hands with antibacterial soap. It can be concluded that the respondents who washed their hands using antibacterial were 50 people consisting of 25 men and 25 women who were determined by lottery. Male respondents who experienced an increase in bacterial expansion totaled 7 (28%) and 18 (72%) experienced a reduction in bacterial expansion. Female respondents experienced an increase in bacterial expansion by 3 (12%) and 22 (88%) subjects experienced a reduction in bacterial expansion agar media.